Green Pesantren : An Islamic Model of Environmental Responsible (Case Study of Pondok Pesantren al Qodir and al Imdad Yogyakarta) - Jayadi, Akhmad; Mikhriani (International Journal of Psychosocial Rehabilitation, 2020)
There are many Koranic verses revealed the environmental responsible. Those confirmed the ancient history recorded that human being creates the great civilization by building a green environment. It shows how to build green space and conserving forest, to keep an unpolluted air and water, and to make a healthy environment. This paper studied an Islamic approach of conservation management in empirical experiences of Pondok Pesantren (PP) in Special Region of Yogyakarta. PP al Qodir and PP al Imdad implement a Maqasid al-Syariah concept as main Islamic pillars with goals like keeping sustainability and the existence and continuity of human life. It means that Islam has serious concern over good environment and its impact on health and wellbeing. According to Islamic model of environmental responsible, the destructive behaviors cause a damage just toward a single part of the environment are as bad as those destruct all of it. Therefore, that responsibility as well as Koranic directions depicted within its verses is a duty for Muslim people.